Sustainable Ecotourism In Keranggan Village: Economic, Socio-Cultural, And Environmental Insights - Novita Uki Hutami; Nihan Anindyaputra Lanisy (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Ecotourism development is considering as a part of implementation of sustainable tourism development that emphasizes on community empowerment for achieving the equality of economic growth, socio-cultural improvement, and environment sustainability. This study aims to analyze the economic, socio-cultural, and environmental impacts on the management of Keranggan Village Ecotourism. The researchers conduct quantitative research by collecting primary data with questionnaires on 100 tourism workers in Keranggan Recency that uses the analysis technique of Structural Equation Model- Partial Least Square (SEM-PLS) 4.0. Based on hipotesis test, economic factors are not the most important, meanwhile socio cultural and environmental factors are the main factors for the sustainability of community based ecotourism. In order to achieve the sustainability, it is necessary to increase the infrastruktur for educating and training as well as empowering the community.